The effect of printing velocity on the temperature and viscosity of the polymer thread at the nozzle exit in 3D printers - Baeza-Campuzano, Alberto; Castaño, Victor M. (Polimery, 2021)
Fused Deposition Modelling (FDM) is a powerful method for advanced additive manufacturing of polymeric materials, due to its simplicity and low cost. However, the process implies complex phenomena which are not fully understood yet. In particular, the effect of viscosity on the printed thread is a key parameter to control if good quality products are to be obtained. Experimental data of two grades of acrylonitrile-butadiene- styrene copolymer (ABS) was employed to analyse, by using ANSYS Fluent simulation package, six printing velocities at a temperature of 230°C. A drastic temperature change was observed as the printing velocity increases, confirming the effect of viscosity on the shear created on the wall of the nozzle transversal to the printing bed. The polymers analysed present different viscosity behavior even under the same angular frequency range (0.1 to 100 rad/s), and testing temperature (230°C), which could lead to inhomogeneities. Our results allow taking into account these parameters as part of the design criteria.